Haruskah Penyidik Pegawai Negeri Sipil Menjadi Jabatan Fungsional? - Felix Aglen Ndaru (Jurnal Bina Praja, 2024)
Civil servant investigators are the vanguard in criminal law enforcement based on sectoral laws. The performance of civil servant investigators in Indonesia is not optimal, among other factors, due to minimal incentives, unclear career paths, and investigators who are not actively conducting investigations. In response to this problem, the Ministry of Law proposed making civil servant investigators a functional position; however, it is currently delayed due to a moratorium imposed by the Ministry of State Apparatus Empowerment and Bureaucratic Reform on the formation of new functional positions. This study is a normative and descriptive legal research and uses job stress theory as a reference. The study aims to assess the urgency of establishing a functional position for civil servant investigators through observations at the Ministry of Environment and Forestry in the 2015-2024 period. The results indicate that civil servant investigators need to be in a functional position based on the analysis of operational and organizational stress. From the operational stress perspective, the duties of civil servant investigators are fraught with risks, ranging from physical asset risks, human resource asset risks, financial asset risks, legal risks, reputation risks, and psychosocial risks. From an organizational stress aspect, the workload of civil servant investigators is considered high because they are required to handle at least four cases a year. The workload becomes more intense because civil servant investigators are required to investigate cases of money laundering. Related to operational stress and organizational stress, civil servant investigators need to be equipped with the internalization of the integrity system, as well as the provision of management support and operational support. Becoming a civil servant investigator is expected to be a promising career for civil servants.